Orientacja austro-polska wobec kwestii ukraińskiej w czasie I wojny światowej (do Aktu 5 listopada 1916 r.) - Mateusz Drozdowski (Ksiegarnia Akademicka Publishing, 2021)
Attitude of politics representing Austro-Polish solution towards Ukrainian question in the time of World War I (before the Act of 5th November)